Expansion of the clinical spectrum associated with AARS2‐related disorders. Issue 8 (17th May 2019) - Srivastava, Siddharth; Butala, Ankur; Mahida, Sonal; Richter, John; Mu, Weiyi; Poretti, Andrea; Vernon, Hilary; VanGerpen, Jay; Atwal, Paldeep S.; Middlebrooks, Erik H.; Zee, David S.; Naidu, SakkuBai
Abstract: Biallelic pathogenic variants in AARS2, a gene encoding the mitochondrial alanyl‐tRNA synthetase, result in a spectrum of findings ranging from infantile cardiomyopathy to adult‐onset progressive leukoencephalopathy. In this article, we present three unrelated individuals with novel compound heterozygous pathogenic AARS2 variants underlying diverse clinical presentations. Patient 1 is a 51‐year‐old man with adult‐onset progressive cognitive, psychiatric, and motor decline and leukodystrophy. Patient 2 is a 34‐year‐old man with childhood‐onset progressive tremor followed by the development of polyneuropathy, ataxia, and mild cognitive and psychiatric decline without leukodystrophy on imaging. Patient 3 is a 57‐year‐old woman with childhood‐onset tremor and nystagmus which preceded dystonia, chorea, ataxia, depression, and cognitive decline marked by cerebellar atrophy and white matter disease. These cases expand the clinical heterogeneity of AARS2‐ related disorders, given that the first and third case represent some of the oldest known survivors of this disease, the second is adult‐onset AARS2 ‐related neurological decline without leukodystrophy, and the third is biallelic AARS2 ‐related disorder involving a partial gene deletion.